2021
DOI: 10.3390/agriculture11050379
|View full text |Cite
|
Sign up to set email alerts
|

Segregation Distortion for Male Parents in High Density Genetic Maps from Reciprocal Crosses between Two Self-Incompatible Cultivars Confirms a Gametophytic System for Self-Incompatibility in Citrus

Abstract: Self-incompatibility is an important evolutionary feature in angiosperms and has major implications for breeding strategies in horticultural crops. In citrus, when coupled with parthenocarpy, it enables the production of seedless fruits in a mono-varietal orchard. A gametophytic incompatibility system with one S locus was proposed for citrus, but its molecular mechanisms remain the subject of debate. The objective of this work was to locate the S locus by the analyzing segregation distortion in reciprocal cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…Based on the ratio 1:1 (SC:SI) of the hybrids obtained from Satsuma x 'Ellendale' cross, this author suggested two different self-incompatible alleles (S Y and S Z ) in 'Ellendale' which differs from the S X allele proposed for Satsuma. Recently, based on segregation distortion for male parents in high density genetic maps from reciprocal crosses between 'Ellendale' and 'Fortune', Ollitrault et al [56] concluded that 'Ellendale' and 'Fortune' share a common self-incompatible allele and confirmed the location of the S locus at the beginning of the chromosome 7 of the Clementine reference genome. From the haplotype sequence analysis on the surrounding genomic region the same authors concluded that 'Ellendale' share the same two self-incompatible alleles as Clementine as already proposed by Kim et al [57] from crosses with homozygous lines for self-incompatible alleles.…”
Section: Self-incompatibilitymentioning
confidence: 99%
“…Based on the ratio 1:1 (SC:SI) of the hybrids obtained from Satsuma x 'Ellendale' cross, this author suggested two different self-incompatible alleles (S Y and S Z ) in 'Ellendale' which differs from the S X allele proposed for Satsuma. Recently, based on segregation distortion for male parents in high density genetic maps from reciprocal crosses between 'Ellendale' and 'Fortune', Ollitrault et al [56] concluded that 'Ellendale' and 'Fortune' share a common self-incompatible allele and confirmed the location of the S locus at the beginning of the chromosome 7 of the Clementine reference genome. From the haplotype sequence analysis on the surrounding genomic region the same authors concluded that 'Ellendale' share the same two self-incompatible alleles as Clementine as already proposed by Kim et al [57] from crosses with homozygous lines for self-incompatible alleles.…”
Section: Self-incompatibilitymentioning
confidence: 99%
“…It is necessary to develop a variety that can not only be consumed raw but also cultivated for ornamental purposes and processed with enhanced functionality [ 1 , 2 , 3 , 4 , 5 ]. The improvement of citrus varieties through traditional crosses is difficult due to inherent biological factors, such as apomixis, self- and cross-incompatibility, long seedling periods, and high heterozygosity [ 6 , 7 , 8 ]. Several single-embryonic varieties of the mandarin lineage exist, which facilitate traditional breeding, although mandarin breeding by artificial mutagenesis is also performed.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kim et al [48], clementines contain S3S11 SI alleles and, in line with the above-indicated hypothesis, only heteroallelic pollen grains can grow through the pistil to fertilize ovules producing heterozygous tetraploid hybrids. This hypothesis should be tested in larger tetraploid progenies obtained by selfing and by the analysis of molecular marker segregation, taking advantage of the SNP markers recently identified in the close vicinity of the citrus S locus located at the beginning of chromosome 7 of the clementine reference genome [27]. As part of our breeding program [45], tetraploid plants of the self-incompatible genotypes 'Chandler' pummelo and 'Moncada' mandarin have been obtained using the same above-described colchicine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies analyzed the segregation of markers of S-RNase genes in controlled progenies and found segregations in agreement with this system for some. Based on segregation distortion from reciprocal crosses on high-density genetic maps, Ollitrault et al [27] confirmed the location of the SI locus at the beginning of chromosome 7 of the clementine reference genome.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation